Resin particles, conductive particles, conductive materials and connection structures

Resin particles with optimized OH- ion intensity ratios and compression moduli, enhanced by crosslinkable compounds and polar functional groups, address high connection resistance and aggregation issues, ensuring reliable low-pressure electrode connections and preventing substrate distortion in liquid crystal display devices.

JP7606348B2Active Publication Date: 2024-12-25SEKISUI CHEMICAL CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2020558069
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-05-14
Filing Date
2020-05-14
Publication Date
2024-12-25
Estimated Expiration
2040-05-14

AI Technical Summary

Technical Problem

Conventional resin particles used in anisotropic conductive materials face challenges such as high connection resistance, aggregation, and poor adhesion with conductive parts when used at low pressure for electrode connections, leading to issues like distorted flexible substrates and display unevenness in liquid crystal display devices.

Method used

The development of resin particles with specific OH- ion intensity ratios and compression moduli, enhanced by crosslinkable compounds and polar functional groups, which improve adhesion and prevent aggregation, thereby reducing connection resistance and maintaining a uniform dispersion state.

Benefits of technology

The resin particles effectively suppress aggregation, enhance adhesion with conductive parts, and lower connection resistance, ensuring reliable electrical connections even at low pressures, thus preventing substrate distortion and display defects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007606348000005
    Figure 0007606348000005
  • Figure 0007606348000006
    Figure 0007606348000006
  • Figure 0007606348000007
    Figure 0007606348000007
Patent Text Reader

Abstract

The present invention provides resin particles which are able to be effectively suppressed in aggregation, and which are capable of effectively enhancing adhesion to conductive parts if conductive particles are obtained by forming the conductive parts on the surfaces of the resin particles so as to be used for electrical connection between electrodes, while being also capable of effectively lowering the connection resistance. With respect to the resin particles according to the present invention, the ratio of the OH- ion strength to the total strength of all negative ions in the outer surfaces of the resin particles is 2.0 × 10-2 or more if a negative spectrum is obtained by means of time-of-flight secondary ion mass spectrometry.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a resin particle that is a polymer of a polymerizable component. The present invention also relates to a conductive particle, a conductive material, and a connection structure using the resin particle. [Background technology]

[0002] Anisotropic conductive materials such as anisotropic conductive pastes and anisotropic conductive films are widely known, in which conductive particles are dispersed in a binder resin.

[0003] The anisotropic conductive material is used to electrically connect the electrodes of various connection target members such as flexible printed circuit boards (FPCs), glass substrates, glass epoxy substrates, and semiconductor chips, and to obtain a connection structure. In addition, as the conductive particles, conductive particles having a base particle and a conductive layer disposed on the surface of the base particle may be used. As the base particle, resin particles may be used.

[0004] As an example of the conductive particles, Patent Document 1 below discloses metal-coated fine particles comprising synthetic resin fine particles and a metal film formed on the surface thereof. In the metal-coated fine particles, the synthetic resin fine particles are made of a copolymer obtained by polymerizing a monomer mixture containing a carboxyl group-containing monomer and a polyfunctional monomer.

[0005] In addition, various adhesives are used to bond two connection target members (adherends). In order to make the thickness of the adhesive layer formed by the adhesive uniform and to control the distance (gap) between the two connection target members (adherends), a gap material (spacer) may be mixed into the adhesive. Resin particles may be used as the gap material (spacer). [Prior art documents] [Patent documents]

[0006] [Patent Document 1] Japanese Patent Application Publication No. 10-259253 Summary of the Invention [Problem to be solved by the invention]

[0007] In recent years, when electrodes are electrically connected using a conductive material or a connecting material containing conductive particles, it is desired to reliably electrically connect the electrodes and reduce the connection resistance even at a relatively low pressure. For example, in a manufacturing method of a liquid crystal display device, when a flexible substrate is mounted in the FOG method, an anisotropic conductive material is placed on a glass substrate, the flexible substrate is laminated, and thermocompression bonding is performed. In recent years, the frame of a liquid crystal panel has become narrower and the glass substrate has become thinner. In this case, if thermocompression bonding is performed at high pressure and high temperature when the flexible substrate is mounted, distortion may occur in the flexible substrate, resulting in display unevenness. Therefore, when a flexible substrate is mounted in the FOG method, it is desirable to perform thermocompression bonding at a relatively low pressure. In addition, even in methods other than the FOG method, it is sometimes required to relatively reduce the pressure and temperature during thermocompression bonding.

[0008] When using conventional resin particles as conductive particles, the connection resistance may increase when electrodes are electrically connected at a relatively low pressure. The cause of this may be that the conductive particles do not contact the electrodes (adherends) sufficiently, or that the adhesion between the resin particles and the conductive parts arranged on the surfaces of the resin particles is low, causing the conductive parts to crack or peel off. Conventional resin particles have limitations in improving the adhesion between the resin particles and the conductive parts arranged on the surfaces of the resin particles, and it may be difficult to sufficiently increase the adhesion between the resin particles and the conductive parts arranged on the surfaces of the resin particles.

[0009] In addition, when conventional resin particles are used to form a conductive portion (plating layer) by plating, the resin particles may aggregate with each other, making it difficult to perform plating well. As a result, the particle size of the conductive particles may vary, and the thickness of the conductive portion of the conductive particles may vary, causing the conductive particles to not contact the electrodes uniformly, resulting in high connection resistance.

[0010] In addition, when conventional resin particles are used as gap materials (spacers), it is difficult to maintain a good dispersion state, and the resin particles may aggregate with each other. In addition, with conventional resin particles, the resin particles may not contact the connection target member (adherend) sufficiently, and a sufficient gap control effect may not be obtained.

[0011] The object of the present invention is to provide a resin particle that can effectively suppress aggregation, and when electrodes are electrically connected using conductive particles having a conductive portion formed on the surface, can effectively increase adhesion with the conductive portion and can effectively reduce connection resistance. Another object of the present invention is to provide a conductive particle, a conductive material, and a connection structure using the above resin particle. [Means for solving the problem]

[0012] According to a broad aspect of the present invention, when a negative spectrum is obtained by time-of-flight secondary ion mass spectrometry on the outer surface of a resin particle, the ratio of OH to the total intensity of all negative ions is - The ratio of ion intensities is 2.0 x 10 -2 Thus, resin particles are provided.

[0013] In a specific aspect of the resin particles according to the present invention, the compressive elastic modulus when compressed by 10% is 500 N / mm 2More than 4500N / mm 2 The following is the result.

[0014] In a specific aspect of the resin particles according to the present invention, the compressive elastic modulus when compressed by 30% is 300 N / mm 2 More than 4000N / mm 2 The following is the result.

[0015] In a specific aspect of the resin particles according to the present invention, the resin particles are a polymer of a polymerizable component containing a plurality of polymerizable compounds.

[0016] In a specific aspect of the resin particles according to the present invention, the polymerizable component constituting the polymer contains a crosslinkable compound, and the content of the crosslinkable compound in 100% by weight of the polymerizable component is 30% by weight or more.

[0017] In a specific aspect of the resin particles according to the present invention, the polymerizable component constituting the polymer contains a crosslinkable compound and a polymerizable compound having a polar functional group, the content of the crosslinkable compound in 100% by weight of the polymerizable component is less than 30% by weight, and the content of the polymerizable compound having a polar functional group in 100% by weight of the polymerizable component is 0.5% by weight or more and 30% by weight or less.

[0018] In a specific aspect of the resin particles according to the present invention, the polymerizable compound having a polar functional group includes a polymerizable compound having a hydroxyl group, a polymerizable compound having a carboxyl group, or a polymerizable compound having a phosphate group.

[0019] In a specific aspect of the resin particles according to the present invention, the crosslinkable compound includes divinylbenzene, tetramethylene glycol di(meth)acrylate, 1,4-butanediol di(meth)acrylate, pentaerythritol tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, glycerin di(meth)acrylate, or 2-(meth)acryloyloxyethyl acid phosphate.

[0020] In a particular aspect of the resin particles according to the present invention, the resin particles are used as spacers, or are used to obtain conductive particles having a conductive portion by forming a conductive portion on the surface of the resin particles.

[0021] According to a broad aspect of the present invention, there is provided a conductive particle comprising the above-described resin particle and a conductive portion disposed on a surface of the resin particle.

[0022] In a specific aspect of the conductive particle according to the present invention, the conductive particle further includes an insulating material disposed on an outer surface of the conductive portion.

[0023] In a specific aspect of the conductive particle according to the present invention, the conductive particle has protrusions on an outer surface of the conductive portion.

[0024] According to a broad aspect of the present invention, there is provided a conductive material comprising conductive particles and a binder resin, the conductive particles comprising the above-mentioned resin particles and a conductive portion disposed on a surface of the resin particles.

[0025] According to a broad aspect of the present invention, there is provided a connection structure comprising: a first connection target member having a first electrode on its surface; a second connection target member having a second electrode on its surface; and a connection portion connecting the first connection target member and the second connection target member, wherein the connection portion is formed from conductive particles or from a conductive material containing the conductive particles and a binder resin, the conductive particles comprise the above-mentioned resin particles and a conductive portion arranged on the surface of the resin particles, and the first electrode and the second electrode are electrically connected by the conductive particles. Effect of the Invention

[0026] In the resin particles according to the present invention, when a negative spectrum is obtained by time-of-flight secondary ion mass spectrometry, the ratio of OH to the total intensity of all negative ions on the outer surface of the resin particles is - The ratio of ion intensities is 2.0 x 10 -2 Since the resin particles according to the present invention have the above-mentioned configuration, aggregation can be effectively suppressed, and when electrodes are electrically connected using conductive particles having conductive parts formed on their surfaces, adhesion to the conductive parts can be effectively increased, and further, connection resistance can be effectively reduced. [Brief description of the drawings]

[0027] [Figure 1] FIG. 1 is a cross-sectional view showing a conductive particle according to a first embodiment of the present invention. [Diagram 2] FIG. 2 is a cross-sectional view showing a conductive particle according to a second embodiment of the present invention. [Diagram 3] FIG. 3 is a cross-sectional view showing a conductive particle according to a third embodiment of the present invention. [Figure 4] FIG. 4 is a cross-sectional view showing an example of a connection structure using conductive particles according to the first embodiment of the present invention. [Diagram 5] FIG. 5 is a cross-sectional view showing an example of an electronic component device using the resin particles according to the present invention. [Figure 6] FIG. 6 is an enlarged cross-sectional view showing a joint portion of the electronic component device shown in FIG. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0028] The present invention will be described in detail below.

[0029] (Resin particles) In the resin particles according to the present invention, when a negative spectrum is obtained by time-of-flight secondary ion mass spectrometry, the ratio of OH to the total intensity of all negative ions on the outer surface of the resin particles is - The ratio of ion intensities is 2.0 x 10 -2 That's all.

[0030] Since the resin particles according to the present invention have the above-mentioned configuration, aggregation can be effectively suppressed, and when electrodes are electrically connected using conductive particles having conductive portions formed on their surfaces, adhesion with the conductive portions can be effectively increased, and further, the connection resistance can be effectively reduced.

[0031] In the resin particles according to the present invention, when a negative spectrum is obtained by time-of-flight secondary ion mass spectrometry, OH -Since the strength of the ions satisfies a specific relationship, a relatively large number of hydroxyl groups can be arranged on the outer surface of the resin particles. When hydroxyl groups are arranged on the outer surface of the resin particles, the adhesion between the resin particles and the conductive part can be increased by the interaction with the hydroxyl groups, and the occurrence of cracks in the conductive part and peeling of the conductive part can be effectively suppressed. In addition, in the conductive particles using the resin particles according to the present invention, the connection resistance between the electrodes can be effectively reduced, and the connection reliability between the electrodes can be effectively improved. For example, even if a connection structure in which electrodes are electrically connected by the conductive particles using the resin particles according to the present invention is left for a long time under high temperature and high humidity conditions, the connection resistance is less likely to increase and the conduction failure is less likely to occur.

[0032] Furthermore, the resin particles according to the present invention can effectively suppress the aggregation of the resin particles. As a result, when the resin particles according to the present invention are used as a gap material (spacer), the dispersion state can be kept good and the particle diameter of the spacer can be made uniform. Furthermore, the resin particles can be sufficiently contacted with the connection target member, etc., and a sufficient gap control effect can be obtained.

[0033] In the resin particles according to the present invention, when a negative spectrum is obtained by time-of-flight secondary ion mass spectrometry (TOF-SIMS) on the outer surface of the resin particles, the ratio of OH to the total intensity of all negative ions is - Ratio of ion intensities (OH - The intensity of the negative ions / total intensity of all negative ions is 2.0×10 -2 That's all.

[0034] In the TOF-SIMS measurement, the outer surface of the resin particle was sputtered twice, and the ratio (OH - The ratio (OH ion intensity / total negative ion intensity) is measured. 40 to 60 of the above resin particles are dispersed in an area of ​​500 μm x 500 μm, and the ratio is measured until the cumulative number of detections reaches 50 (OH ion intensity / total negative ion intensity).- The average value of the intensity of OH ions / total intensity of all negative ions) is used. If it is difficult to arrange 40 to 60 particles in an area of ​​500 μm × 500 μm due to the size of the resin particles, the number of particles arranged may be appropriately reduced for measurement. In the above measurement, for example, a measurement result of an area of ​​about 2 nm thickness from the outer surface of the resin particle toward the inside is obtained. In addition, in the above measurement, the ratio (OH - It is preferable to calculate the above ratio by arithmetically averaging the intensities of the negative ions (intensity of the negative ions / total intensities of all negative ions).

[0035] Above ratio (OH - The intensity of the negative ions / total intensity of all negative ions) is preferably 2.5×10 -2 More preferably, 3.0×10 -2 Above ratio (OH - The upper limit of the ratio (OH ion intensity / total negative ion intensity) is not particularly limited. - The intensity of the negative ions / total intensity of all negative ions is 9.0 x 10 -2 or less. When the resin particles satisfy the above-mentioned preferred aspects, aggregation can be suppressed more effectively. In addition, when the resin particles satisfy the above-mentioned preferred aspects, when electrodes are electrically connected using conductive particles having conductive parts formed on the surfaces, adhesion to the conductive parts can be increased more effectively, and further, connection resistance can be reduced more effectively.

[0036] The TOF-SIMS used is a TOF-SIMS 5 model manufactured by ION TOF. The OH groups on the outer surfaces of the resin particles are analyzed using a TOF-SIMS analyzer. - To measure the ionic strength and total ionic strength, for example, Bi 3+An ion gun is used as the primary ion source for measurement, and measurements can be performed under conditions of 25 keV. Sputtering is a method in which an inert gas such as argon is introduced into a vacuum, a negative voltage is applied to the target to generate a glow discharge, ionizing the inert gas atoms, and the gas ions collide with the surface of the target at high speed to violently strike the surface. The surface of the target can be ground to a depth on the order of nanometers to micrometers. Specifically, for example, O2 + By performing sputtering using OH, it is possible to dig into the surface of the resin particle at a depth of about 1 nm per step. By performing two sputtering steps, TOF-SIMS was used to measure OH in a region about 2 nm thick from the outer surface of the resin particle toward the inside. - The ratio of the intensity of an ion to the total ionic intensity can be measured.

[0037] The compressive elastic modulus (10% K value) when the resin particles are compressed by 10% is preferably 500 N / mm 2 More preferably, 1000N / mm 2 More than 6000N / mm 2 Less than or equal to 5000N / mm 2 Less than 4500N / mm 2 Below 3500N / mm 2 or less. When the 10% K value is equal to or more than the lower limit and equal to or less than the upper limit, aggregation can be suppressed more effectively. Furthermore, when the 10% K value is equal to or more than the lower limit and equal to or less than the upper limit, when electrodes are electrically connected using conductive particles having conductive parts formed on their surfaces, adhesion to the conductive parts can be increased more effectively, and further, connection resistance can be reduced more effectively.

[0038] The compressive elastic modulus (30% K value) when the resin particles are compressed by 30% is preferably 300 N / mm 2 More preferably, 500N / mm 2 or more, preferably 5500N / mm2 Less than or equal to 4500N / mm 2 Less than 4000N / mm 2 Below 3000N / mm 2 or less. When the 30% K value is equal to or more than the lower limit and equal to or less than the upper limit, aggregation can be suppressed more effectively. Furthermore, when the 30% K value is equal to or more than the lower limit and equal to or less than the upper limit, when electrodes are electrically connected using conductive particles having conductive parts formed on their surfaces, adhesion to the conductive parts can be increased more effectively, and further, connection resistance can be reduced more effectively.

[0039] The compressive elastic modulus (10% K value and 30% K value) of the resin particles can be measured as follows.

[0040] Using a micro-compression tester, one resin particle is compressed with a cylindrical (diameter 50 μm, made of diamond) smooth indenter end face under the conditions of 25° C., compression speed 0.3 mN / sec, and maximum test load 20 mN. The load value (N) and compression displacement (mm) at this time are measured. From the obtained measured value, the compression modulus (10% K value or 30% K value) can be calculated by the following formula. As the micro-compression tester, for example, Fischer Scope H-100 manufactured by Fischer is used. The compression modulus (10% K value or 30% K value) of the resin particle is preferably calculated by arithmetic averaging of the compression modulus (10% K value or 30% K value) of 50 arbitrarily selected resin particles.

[0041] 10% K value or 30% K value (N / mm 2 )=(3 / 2 1 / 2 )·F·S -3 / 2 ·R -1 / 2 F: Load value (N) when resin particles are compressed by 10% or 30% S: Compressive displacement (mm) when the resin particles are compressed by 10% or 30% R: Radius of resin particle (mm)

[0042] The compressive elastic modulus universally and quantitatively represents the hardness of the resin particles. By using the compressive elastic modulus, the hardness of the resin particles can be quantitatively and unambiguously represented.

[0043] The compression recovery rate of the resin particles is preferably 5% or more, more preferably 10% or more, and preferably 60% or less, more preferably 45% or less. When the compression recovery rate is equal to or more than the lower limit and equal to or less than the upper limit, aggregation can be more effectively suppressed. When the compression recovery rate is equal to or more than the lower limit and equal to or less than the upper limit, when electrodes are electrically connected using conductive particles having conductive parts formed on their surfaces, adhesion to the conductive parts can be more effectively increased, and further, connection resistance can be more effectively reduced.

[0044] The compression recovery rate of the resin particles can be measured as follows.

[0045] Resin particles are scattered on a sample stage. A micro-compression tester is used to apply a load (reversed load value) to each scattered resin particle at 25°C toward the center of the resin particle with the smooth end face of a cylinder (diameter 50 μm, made of diamond) until the resin particle is compressed and deformed by 30%. The load is then removed to the load value for the origin (0.40 mN). The load-compression displacement during this period is measured, and the compression recovery rate can be calculated from the following formula. The loading speed is 0.33 mN / sec. For example, a Fischerscope H-100 manufactured by Fischer is used as the micro-compression tester.

[0046] Compression recovery rate (%) = [L2 / L1] x 100 L1: Compressive displacement from the load value for the origin to the load value for the reverse load when applying a load L2: Unloading displacement from the reverse load value when releasing the load to the load value for the origin

[0047] The use of the resin particles is not particularly limited. The resin particles can be suitably used for various applications. The resin particles are preferably used as spacers, or to obtain conductive particles having the conductive part by forming a conductive part on the surface. In the conductive particles, the conductive part is formed on the surface of the resin particles. The resin particles are preferably used to obtain conductive particles having the conductive part by forming a conductive part on the surface. The conductive particles are preferably used to electrically connect between electrodes. The conductive particles may be used as a gap material (spacer). The resin particles are preferably used as a gap material (spacer). Examples of the method of using the gap material (spacer) include spacers for liquid crystal display elements, gap control spacers, and stress relaxation spacers. The gap control spacers can be used for gap control of stacked chips and electronic component devices to ensure standoff height and flatness, and gap control of optical components to ensure smoothness of glass surfaces and thickness of adhesive layers. The stress relaxation spacers can be used for stress relaxation of sensor chips, etc., and stress relaxation of connection parts connecting two connection target members. In addition, when the resin particles are used as a gap material (spacer), the dispersion state can be kept good, the particle size of the spacer can be made uniform, and the particles can be brought into sufficient contact with the connection target member, etc., to obtain a sufficient gap control effect.

[0048] The resin particles are preferably used as spacers for liquid crystal display elements, and are preferably used in a peripheral sealant for liquid crystal display elements. In the peripheral sealant for liquid crystal display elements, the resin particles preferably function as spacers. The resin particles have good compressive deformation characteristics and good compressive fracture characteristics, so when the resin particles are used as spacers to be arranged between substrates, or when a conductive part is formed on the surface and the resin particles are used as conductive particles to electrically connect between electrodes, the spacers or conductive particles are efficiently arranged between substrates or between electrodes. Furthermore, the resin particles can suppress scratches on liquid crystal display element members, etc., so that connection defects and display defects are less likely to occur in liquid crystal display elements using the spacers for liquid crystal display elements and connection structures using the conductive particles.

[0049] Furthermore, the resin particles can be suitably used as an inorganic filler, a toner additive, a shock absorber, or a vibration absorber, for example, as a substitute for rubber or springs.

[0050] Other details of the resin particles will be described below.

[0051] (Other details of resin particles) The resin particles are preferably polymers of polymerizable components containing a plurality of polymerizable compounds. In the resin particles, the center of the resin particles and the surface of the resin particles are preferably composed of the same polymerizable components. The blending ratio of the polymerizable components in the center of the resin particles and the blending ratio of the polymerizable components in the surface of the resin particles may be the same or different. The composition ratio of the components in the center of the resin particles and the composition ratio of the components in the surface of the resin particles may be the same or different. When the resin particles satisfy the above preferred aspects, aggregation can be suppressed more effectively. In addition, when the resin particles satisfy the above preferred aspects, when electrodes are electrically connected using conductive particles having conductive parts formed on the surfaces, the adhesion with the conductive parts can be more effectively increased, and further, the connection resistance can be more effectively reduced.

[0052] In the above resin particles, the center of the resin particle is preferably formed by the center-forming material, and the surface of the resin particle is preferably formed by the surface-forming material. In the above resin particles, the components of the above center-forming material and the above surface-forming material are preferably the same. In the above resin particles, the component ratio of the above center-forming material and the component ratio of the above surface-forming material may be the same or different. In addition, in the above resin particles, it is preferable that there is a region containing both the above center-forming material and the above surface-forming material. In the above resin particles, it is preferable that the resin particles have a region in the center that contains the above center-forming material and does not contain the above surface-forming material or contains the above surface-forming material at less than 25% by weight. In the above resin particles, it is preferable that the resin particles have a region in the surface that contains the above surface-forming material and does not contain the above center-forming material or contains the above center-forming material at less than 25% by weight. When the above resin particles satisfy the above preferred aspects, aggregation can be suppressed more effectively. Furthermore, when the resin particles satisfy the above-mentioned preferred aspects, when electrodes are electrically connected using conductive particles having conductive portions formed on their surfaces, the adhesion with the conductive portions can be increased even more effectively, and further, the connection resistance can be reduced even more effectively.

[0053] The resin particles are preferably not core-shell particles having a core and a shell arranged on the surface of the core, and preferably have no interface between the core and the shell within the resin particles. The resin particles are preferably not interfaced within the resin particles, and more preferably have no interface where different surfaces are in contact with each other. The resin particles are preferably not discontinuous where a surface is present, and preferably have no discontinuous where a structural surface is present. When the resin particles satisfy the above preferred aspects, aggregation can be suppressed more effectively. In addition, when the resin particles satisfy the above preferred aspects, when electrodes are electrically connected using conductive particles having a conductive part formed on the surface, the adhesion with the conductive part can be more effectively increased, and further, the connection resistance can be more effectively reduced.

[0054] In the resin particles, the polymerizable component constituting the polymer preferably contains a crosslinkable compound. When the polymerizable component constituting the polymer contains a crosslinkable compound, the content of the crosslinkable compound is preferably 30% by weight or more, more preferably 40% by weight or more, in 100% by weight of the polymerizable component. The upper limit of the content of the crosslinkable compound is not particularly limited. The content of the crosslinkable compound is preferably 80% by weight or less, more preferably 70% by weight or less, and even more preferably 60% by weight or less. When the resin particles satisfy the above preferred aspects, aggregation can be suppressed more effectively. In addition, when the resin particles satisfy the above preferred aspects, when electrodes are electrically connected using conductive particles having a conductive part formed on the surface, the adhesion with the conductive part can be more effectively increased, and further, the connection resistance can be more effectively reduced.

[0055] In the resin particles, the polymerizable component constituting the polymer may be either a polymerizable component containing a crosslinkable compound having no polar functional group and not containing a crosslinkable compound having a polar functional group, or a polymerizable component containing a crosslinkable compound having no polar functional group and a crosslinkable compound having a polar functional group. In the resin particles, the polymerizable component constituting the polymer may be a polymerizable component containing a crosslinkable compound having no polar functional group and not containing a crosslinkable compound having a polar functional group. In the resin particles, the polymerizable component constituting the polymer may be a polymerizable component containing a crosslinkable compound having no polar functional group and a crosslinkable compound having a polar functional group.

[0056] When the polymerizable component constituting the polymer contains a crosslinkable compound having no polar functional group and does not contain a crosslinkable compound having a polar functional group, the content of the crosslinkable compound having no polar functional group is preferably 30% by weight or more, more preferably 40% by weight or more, in 100% by weight of the polymerizable component. The upper limit of the content of the crosslinkable compound having no polar functional group is not particularly limited. The content of the crosslinkable compound having no polar functional group is preferably 80% by weight or less, more preferably 70% by weight or less, and even more preferably 60% by weight or less. When the resin particles satisfy the above preferred aspects, aggregation can be suppressed more effectively. In addition, when the resin particles satisfy the above preferred aspects, when electrodes are electrically connected using conductive particles having a conductive portion formed on the surface, adhesion with the conductive portion can be more effectively increased, and further, the connection resistance can be more effectively reduced.

[0057] When the polymerizable component constituting the polymer contains a crosslinkable compound having no polar functional group and a crosslinkable compound having a polar functional group, the total content of the crosslinkable compound having no polar functional group and the crosslinkable compound having a polar functional group is preferably 30% by weight or more, more preferably 40% by weight or more, in 100% by weight of the polymerizable component. The upper limit of the total content of the crosslinkable compound having no polar functional group and the crosslinkable compound having a polar functional group is not particularly limited. The total content of the crosslinkable compound having no polar functional group and the crosslinkable compound having a polar functional group is preferably 80% by weight or less, more preferably 70% by weight or less, and even more preferably 60% by weight or less. When the resin particles satisfy the above preferred aspects, aggregation can be suppressed more effectively. In addition, when the resin particles satisfy the above preferred aspects, when electrodes are electrically connected using conductive particles having a conductive portion formed on the surface, adhesion with the conductive portion can be more effectively increased, and further, the connection resistance can be more effectively reduced.

[0058] In the resin particles, the polymerizable component constituting the polymer preferably contains a crosslinkable compound and a polymerizable compound having a polar functional group. When the polymerizable component constituting the polymer contains a crosslinkable compound and a polymerizable compound having a polar functional group, the content of the crosslinkable compound is preferably less than 30% by weight, more preferably 20% by weight or less, in 100% by weight of the polymerizable component. The lower limit of the content of the crosslinkable compound is not particularly limited. The content of the crosslinkable compound may be 5% by weight or more. When the polymerizable component constituting the polymer contains a crosslinkable compound and a polymerizable compound having a polar functional group, the content of the polymerizable compound having a polar functional group is preferably 0.5% by weight or more, more preferably 2% by weight or more, and preferably 30% by weight or less, more preferably 20% by weight or less, in 100% by weight of the polymerizable component. When the resin particles satisfy the above preferred aspects, aggregation can be suppressed more effectively. Furthermore, when the resin particles satisfy the above-mentioned preferred aspects, when electrodes are electrically connected using conductive particles having conductive portions formed on their surfaces, the adhesion to the conductive portions can be increased even more effectively, and further, the connection resistance can be reduced even more effectively.

[0059] In the resin particles, the polymerizable component constituting the polymer preferably contains a crosslinkable compound having no polar functional group and a polymerizable compound having no crosslinkability and a polar functional group. When the polymerizable component constituting the polymer contains a crosslinkable compound having no polar functional group and a polymerizable compound having no crosslinkability and a polar functional group, the content of the crosslinkable compound having no polar functional group is preferably less than 30% by weight, more preferably 20% by weight or less, in 100% by weight of the polymerizable component. The lower limit of the content of the crosslinkable compound having no polar functional group is not particularly limited. The content of the crosslinkable compound having no polar functional group may be 5% by weight or more. When the polymerizable component constituting the polymer contains a crosslinkable compound having no polar functional group and a polymerizable compound having no crosslinkability and a polar functional group, the content of the polymerizable compound having no crosslinkability and a polar functional group is preferably 0.5% by weight or more, more preferably 2% by weight or more, and preferably 30% by weight or less, more preferably 20% by weight or less, in 100% by weight of the polymerizable component. When the resin particles satisfy the above-mentioned preferred aspects, aggregation can be suppressed more effectively. In addition, when the resin particles satisfy the above-mentioned preferred aspects, when electrodes are electrically connected using conductive particles having conductive parts formed on their surfaces, adhesion to the conductive parts can be more effectively increased, and further, connection resistance can be more effectively reduced.

[0060] In addition, when a negative spectrum is obtained by time-of-flight secondary ion mass spectrometry on the outer surface of the resin particle, the ratio of OH to the total intensity of all negative ions is - The ratio of ion intensities is 2.0 x 10 -2 In order to make it easier to achieve the above, it is preferable that the resin particles satisfy any one of the following relationships. 1) The polymerizable component constituting the polymer contains a crosslinkable compound, and the content of the crosslinkable compound in 100% by weight of the polymerizable component is 30% by weight or more. 2) The polymerizable component constituting the polymer contains a crosslinkable compound and a polymerizable compound having a polar functional group, and in 100% by weight of the polymerizable component, the content of the crosslinkable compound is less than 30% by weight, and the content of the polymerizable compound having the polar functional group is 0.5% by weight or more and 30% by weight or less.

[0061] In particular, in the above 1), when the content of the crosslinkable compound is 30% by weight or more and 80% by weight or less, it is easier to obtain a ratio of OH to the total strength of all negative ions. - The ratio of ion intensities is 2.0 x 10 -2 It can be more than that.

[0062] The above-mentioned polymerizable compound having a polar functional group is not particularly limited. The above-mentioned polar functional group is not particularly limited. Examples of the above-mentioned polar functional group include a hydroxyl group, a carboxyl group, a sulfonic acid group, and a phosphoric acid group. The above-mentioned polymerizable compound having a polar functional group may be used alone or in combination of two or more kinds.

[0063] Examples of the polymerizable compound having a hydroxyl group include 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, glycerin di(meth)acrylate, 2-hydroxy-3-phenoxypropyl (meth)acrylate, 2-hydroxy-3-(meth)acryloyloxypropyl (meth)acrylate, pentaerythritol tri(meth)acrylate, 2-(meth)acryloyloxyethyl-2-hydroxypropyl phthalate, and polyethylene glycol (meth)acrylate.

[0064] Examples of the polymerizable compound having a carboxy group include (meth)acrylic acid, 2-carboxyethyl (meth)acrylate, and 2-(meth)acryloyloxyethyl succinic acid.

[0065] An example of the polymerizable compound having a sulfonic acid group is 3-sulfopropyl(meth)acrylate.

[0066] An example of the polymerizable compound having a phosphoric acid group is 2-(meth)acryloyloxyethyl acid phosphate.

[0067] In the resin particles, the polymerizable compound having a polar functional group preferably includes a polymerizable compound having a hydroxyl group, a polymerizable compound having a carboxyl group, or a polymerizable compound having a phosphoric acid group. In the resin particles, the polymerizable compound having a polar functional group more preferably includes 2-hydroxypropyl (meth)acrylate, (meth)acrylic acid, 2-(meth)acryloyloxyethyl succinic acid, or 2-(meth)acryloyloxyethyl acid phosphate. In the resin particles, the polymerizable compound having a polar functional group more preferably includes (meth)acrylic acid, 2-(meth)acryloyloxyethyl succinic acid, or 2-(meth)acryloyloxyethyl acid phosphate. When the resin particles satisfy the above preferred aspects, aggregation can be suppressed more effectively. In addition, when the resin particles satisfy the above preferred aspects, when electrodes are electrically connected using conductive particles having a conductive portion formed on the surface, adhesion with the conductive portion can be more effectively increased, and further, the connection resistance can be more effectively reduced.

[0068] The crosslinkable compound is not particularly limited. Examples of the crosslinkable compound include divinylbenzene, (di / tri / tetra)methylene glycol (meth)acrylate, (di / tri / tetra)ethylene glycol (meth)acrylate, polytetramethylene glycol di(meth)acrylate, 1,4-butanediol di(meth)acrylate, 1,6-hexanediol (meth)acrylate, 1,9-nonanediol (meth)acrylate, dimethylol-tricyclodecane dimethacrylate, pentaerythritol tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, glycerin di(meth)acrylate, and 2-(meth)acryloyloxyethyl acid phosphate (Kyoeisha Chemical Co., Ltd. "Light Ester P-2M"). The crosslinkable compound may be used alone or in combination of two or more.

[0069] In the resin particles, the crosslinkable compound preferably contains the following compound. Examples of the compound include divinylbenzene, tetramethylene glycol di(meth)acrylate, 1,4-butanediol di(meth)acrylate, pentaerythritol tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, glycerin di(meth)acrylate, and 2-(meth)acryloyloxyethyl acid phosphate (Kyoeisha Chemical Co., Ltd.'s "Light Ester P-2M"). In the resin particles, the crosslinkable compound more preferably contains glycerin di(meth)acrylate, 2-(meth)acryloyloxyethyl acid phosphate (Kyoeisha Chemical Co., Ltd.'s "Light Ester P-2M"), or pentaerythritol tri(meth)acrylate. When the resin particles satisfy the above preferred aspects, aggregation can be suppressed more effectively. Furthermore, when the resin particles satisfy the above-mentioned preferred aspects, when electrodes are electrically connected using conductive particles having conductive portions formed on their surfaces, the adhesion with the conductive portions can be increased even more effectively, and further, the connection resistance can be reduced even more effectively.

[0070] The polymerizable compound having a polar functional group may be a crosslinkable compound. The crosslinkable compound may be a polymerizable compound having a polar functional group. When the polymerizable component includes a compound having crosslinkability, a polar functional group, and polymerizability, the polymerizable compound includes both a crosslinkable compound and a polymerizable compound having a polar functional group. The content of the crosslinkable compound includes the content of the compound having crosslinkability, a polar functional group, and polymerizability. The content of the polymerizable compound having a polar functional group includes the content of the compound having crosslinkability, a polar functional group, and polymerizability.

[0071] In the resin particles, the polymerizable component constituting the polymer does not contain or contains a non-crosslinkable compound. In the resin particles, the polymerizable component constituting the polymer may not contain a non-crosslinkable compound. In the resin particles, the polymerizable component constituting the polymer may contain a non-crosslinkable compound. The non-crosslinkable compound may be a non-crosslinkable compound that does not have a polar functional group. The non-crosslinkable compound may be used alone or in combination of two or more.

[0072] Examples of the non-crosslinkable compound include vinyl compounds such as styrene monomers, α-methylstyrene, and chlorostyrene; vinyl ether compounds such as methyl vinyl ether, ethyl vinyl ether, and propyl vinyl ether; acid vinyl ester compounds such as vinyl acetate, vinyl butyrate, vinyl laurate, and vinyl stearate; halogen-containing monomers such as vinyl chloride and vinyl fluoride; and (meth)acrylic compounds such as methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, lauryl (meth)acrylate, cetyl (meth)acrylate, stearyl (meth)acrylate, cyclohexyl Examples of suitable (meth)acrylate compounds include alkyl (meth)acrylate compounds such as (meth)acrylate and isobornyl (meth)acrylate; oxygen-containing (meth)acrylate compounds such as 2-hydroxyethyl (meth)acrylate, glycerol (meth)acrylate, polyoxyethylene (meth)acrylate, and glycidyl (meth)acrylate; nitrile-containing monomers such as (meth)acrylonitrile; halogen-containing (meth)acrylate compounds such as trifluoromethyl (meth)acrylate and pentafluoroethyl (meth)acrylate; α-olefin compounds such as diisobutylene, isobutylene, linearne, ethylene, and propylene; and conjugated diene compounds such as isoprene and butadiene.

[0073] When the polymerizable component constituting the polymer contains the non-crosslinkable compound, the content of the non-crosslinkable compound in 100% by weight of the polymerizable component may be 1% by weight or more, 5% by weight or more, 10% by weight or more, 20% by weight or more, 30% by weight or more, or 40% by weight or more. When the polymerizable component constituting the polymer contains the non-crosslinkable compound, the content of the non-crosslinkable compound in 100% by weight of the polymerizable component may be 90% by weight or less, 80% by weight or less, 70% by weight or less, 60% by weight or less, or 50% by weight or less.

[0074] The particle diameter of the resin particles can be appropriately set depending on the application. The particle diameter of the resin particles is preferably 0.5 μm or more, more preferably 1 μm or more, and preferably 500 μm or less, more preferably 300 μm or less, even more preferably 100 μm or less, even more preferably 50 μm or less, and particularly preferably 30 μm or less. When the particle diameter of the resin particles is the above lower limit or more and the above upper limit or less, the resin particles can be more suitably used for conductive particles or spacers. When the particle diameter of the resin particles is 0.5 μm or more and 500 μm or less, the resin particles can be suitably used for conductive particles. When the particle diameter of the resin particles is 0.5 μm or more and 500 μm or less, the resin particles can be suitably used for spacers.

[0075] The particle diameter of the resin particles is preferably an average particle diameter, and more preferably a number average particle diameter. The particle diameter of the resin particles is, for example, obtained by observing 50 arbitrary resin particles with an electron microscope or optical microscope and calculating the average particle diameter of each resin particle, or by a particle size distribution measuring device. In the observation with an electron microscope or optical microscope, the particle diameter of each resin particle is obtained as a particle diameter of a circle equivalent diameter. In the observation with an electron microscope or optical microscope, the average particle diameter of 50 arbitrary resin particles with a circle equivalent diameter is almost equal to the average particle diameter of a sphere equivalent diameter. In the particle size distribution measuring device, the particle diameter of each resin particle is obtained as a particle diameter of a sphere equivalent diameter. The average particle diameter of the resin particles is preferably calculated by a particle size distribution measuring device.

[0076] In the case of measuring the particle size of the resin particles in the conductive particles, the measurement can be carried out, for example, as follows.

[0077] The conductive particles are added to Kulzer's Technovit 4000 so that the content of the conductive particles is 30% by weight, and dispersed to prepare a resin body for embedding conductive particles for inspection. An ion milling device (Hitachi High-Technologies' IM4000) is used to cut out a cross section of the conductive particles so that it passes through the center of the conductive particles dispersed in the resin body for inspection. Then, a field emission scanning electron microscope (FE-SEM) is used to set the image magnification to 25,000 times, and 50 conductive particles are randomly selected to observe the resin particles of each conductive particle. The particle diameter of the resin particles in each conductive particle is measured, and the particle diameter of the resin particles is determined by arithmetic averaging.

[0078] The coefficient of variation (CV value) of the particle diameter of the resin particles is preferably 10% or less, more preferably 7% or less. When the coefficient of variation of the particle diameter of the resin particles is equal to or less than the upper limit, the resin particles can be more suitably used for spacers and conductive particles.

[0079] The coefficient of variation (CV value) can be measured as follows.

[0080] CV value (%) = (ρ / Dn) × 100 ρ: Standard deviation of resin particle diameter Dn: average particle size of resin particles

[0081] The shape of the resin particles is not particularly limited, and may be spherical or a shape other than spherical, such as flat.

[0082] (Conductive particles) The conductive particles include the above-mentioned resin particles and conductive portions disposed on the surfaces of the resin particles.

[0083] FIG. 1 is a cross-sectional view showing a conductive particle according to a first embodiment of the present invention.

[0084] The conductive particle 1 shown in Fig. 1 has a resin particle 11 and a conductive portion 2 disposed on the surface of the resin particle 11. The conductive portion 2 is in contact with the surface of the resin particle 11. The conductive portion 2 covers the surface of the resin particle 11. The conductive particle 1 is a coated particle in which the surface of the resin particle 11 is coated with the conductive portion 2. In the conductive particle 1, the conductive portion 2 is a single-layer conductive portion (conductive layer).

[0085] FIG. 2 is a cross-sectional view showing a conductive particle according to a second embodiment of the present invention.

[0086] 2 includes a resin particle 11 and a conductive portion 22 disposed on the surface of the resin particle 11. The conductive portion 22 as a whole includes a first conductive portion 22A on the resin particle 11 side and a second conductive portion 22B on the side opposite to the resin particle 11 side.

[0087] The conductive particle 1 shown in Fig. 1 and the conductive particle 21 shown in Fig. 2 are different only in the conductive portion 22. That is, the conductive particle 1 has a conductive portion with a single layer structure, whereas the conductive particle 21 has a first conductive portion 22A and a second conductive portion 22B with a two-layer structure. The first conductive portion 22A and the second conductive portion 22B may be formed as different conductive portions or may be formed as the same conductive portion.

[0088] The first conductive portion 22A is disposed on the surface of the resin particle 11. The first conductive portion 22A is disposed between the resin particle 11 and the second conductive portion 22B. The first conductive portion 22A is in contact with the resin particle 11. The second conductive portion 22B is in contact with the first conductive portion 22A. The first conductive portion 22A is disposed on the surface of the resin particle 11, and the second conductive portion 22B is disposed on the surface of the first conductive portion 22A.

[0089] FIG. 3 is a cross-sectional view showing a conductive particle according to a third embodiment of the present invention.

[0090] 3 has a resin particle 11, a conductive portion 32, a plurality of core substances 33, and a plurality of insulating substances 34. The conductive portion 32 is disposed on the surface of the resin particle 11. The plurality of core substances 33 are disposed on the surface of the resin particle 11. The conductive portion 32 is disposed on the surface of the resin particle 11 so as to cover the resin particle 11 and the plurality of core substances 33. In the conductive particle 31, the conductive portion 32 is a single-layer conductive portion (conductive layer).

[0091] The conductive particle 31 has a plurality of protrusions 31a on its outer surface. In the conductive particle 31, the conductive portion 32 has a plurality of protrusions 32a on its outer surface. The plurality of core substances 33 raise the outer surface of the conductive portion 32. The outer surface of the conductive portion 32 is raised by the plurality of core substances 33, thereby forming the protrusions 31a and 32a. The plurality of core substances 33 are embedded in the conductive portion 32. The core substances 33 are disposed inside the protrusions 31a and 32a. In the conductive particle 31, a plurality of core substances 33 are used to form the protrusions 31a and 32a. In the conductive particle, a plurality of the core substances may not be used to form the protrusions. The conductive particle may not have a plurality of the core substances.

[0092] The conductive particle 31 has an insulating material 34 disposed on the outer surface of the conductive portion 32. At least a portion of the outer surface of the conductive portion 32 is covered with the insulating material 34. The insulating material 34 is formed of a material having insulating properties, and is an insulating particle. In this way, the conductive particle according to the present invention may have an insulating material disposed on the outer surface of the conductive portion. However, the conductive particle does not necessarily have to have an insulating material. The conductive particle does not necessarily have to have a plurality of insulating materials.

[0093] Conductive Part: The metal for forming the conductive portion is not particularly limited. Examples of the metal include gold, silver, palladium, copper, platinum, zinc, iron, tin, lead, aluminum, cobalt, indium, nickel, chromium, titanium, antimony, bismuth, thallium, germanium, cadmium, silicon, tungsten, molybdenum, and alloys thereof. Examples of the metal include tin-doped indium oxide (ITO) and solder. From the viewpoint of further increasing the connection reliability between electrodes, the metal is preferably an alloy containing tin, nickel, palladium, copper, or gold, and is preferably nickel or palladium.

[0094] In addition, since the conductive part and the outer surface part of the conductive part contain nickel, it is preferable that the conductive part and the outer surface part of the conductive part contain nickel, since the conductive part can effectively improve the conduction reliability. The nickel content in 100% by weight of the nickel-containing conductive part is preferably 10% by weight or more, more preferably 50% by weight or more, even more preferably 60% by weight or more, even more preferably 70% by weight or more, and particularly preferably 90% by weight or more. The nickel content in 100% by weight of the nickel-containing conductive part may be 97% by weight or more, 97.5% by weight or more, or 98% by weight or more.

[0095] In addition, hydroxyl groups are often present on the surface of the conductive part due to oxidation. In general, hydroxyl groups are present on the surface of the conductive part formed of nickel due to oxidation. An insulating material can be arranged on the surface of the conductive part (surface of the conductive particle) having such hydroxyl groups via chemical bonding.

[0096] The conductive part may be formed of one layer, as in the conductive particles 1 and 31. The conductive part may be formed of multiple layers, as in the conductive particle 21. That is, the conductive part may have a laminated structure of two or more layers. When the conductive part is formed of multiple layers, the outermost layer is preferably a gold layer, a nickel layer, a palladium layer, a copper layer, or an alloy layer containing tin and silver, and more preferably a gold layer. When the outermost layer is one of these preferred conductive parts, the connection resistance between the electrodes can be more effectively reduced. In addition, when the outermost layer is a gold layer, the corrosion resistance can be more effectively increased.

[0097] The method of forming the conductive part on the surface of the resin particle is not particularly limited. The method of forming the conductive part includes, for example, a method by electroless plating, a method by electroplating, a method by physical vapor deposition, and a method of coating the surface of the resin particle with a metal powder or a paste containing a metal powder and a binder. The method by electroless plating is preferred because the conductive part is easily formed. The method by physical vapor deposition includes methods such as vacuum deposition, ion plating, and ion sputtering.

[0098] The particle diameter of the conductive particles is preferably 0.5 μm or more, more preferably 1 μm or more, and preferably 500 μm or less, more preferably 300 μm or less, even more preferably 100 μm or less, even more preferably 50 μm or less, and particularly preferably 30 μm or less. When the particle diameter of the conductive particles is the above lower limit or more and the above upper limit or less, when electrodes are connected using the conductive particles, the contact area between the conductive particles and the electrodes becomes sufficiently large, and when the conductive part is formed, the conductive particles are unlikely to be aggregated. In addition, the gap between the electrodes connected via the conductive particles does not become too large, and the conductive part is unlikely to peel off from the surface of the resin particle. In addition, when the particle diameter of the conductive particles is the above lower limit or more and the above upper limit or less, the conductive particles can be suitably used for the application of conductive materials.

[0099] The particle diameter of the conductive particles means the diameter when the conductive particles are spherical, and means the diameter when the conductive particles are other than spherical, assuming that the conductive particles are a true sphere of equivalent volume.

[0100] The particle diameter of the conductive particles is preferably an average particle diameter, and more preferably a number average particle diameter. The particle diameter of the conductive particles is obtained by observing 50 arbitrary conductive particles with an electron microscope or an optical microscope and calculating the average value, or by a particle size distribution measuring device. In the observation with an electron microscope or an optical microscope, the particle diameter of each conductive particle is obtained as a particle diameter of a circle equivalent diameter. In the observation with an electron microscope or an optical microscope, the average particle diameter of 50 arbitrary conductive particles with a circle equivalent diameter is almost equal to the average particle diameter of a sphere equivalent diameter. In the particle size distribution measuring device, the particle diameter of each conductive particle is obtained as a particle diameter of a sphere equivalent diameter. The particle diameter of the conductive particles is preferably calculated by a particle size distribution measuring device.

[0101] The thickness of the conductive part is preferably 0.005 μm or more, more preferably 0.01 μm or more, and preferably 10 μm or less, more preferably 1 μm or less, and even more preferably 0.3 μm or less. When the conductive part is multi-layered, the thickness of the conductive part is the thickness of the entire conductive part. When the thickness of the conductive part is equal to or more than the lower limit and equal to or less than the upper limit, sufficient conductivity is obtained, and the conductive particles do not become too hard, so that the conductive particles are sufficiently deformed when connecting between electrodes.

[0102] When the conductive part is formed of a plurality of layers, the thickness of the conductive part of the outermost layer is preferably 0.001 μm or more, more preferably 0.01 μm or more, and preferably 0.5 μm or less, more preferably 0.1 μm or less. When the thickness of the conductive part of the outermost layer is equal to or more than the lower limit and equal to or less than the upper limit, the coating of the conductive part of the outermost layer becomes uniform, the corrosion resistance becomes sufficiently high, and the connection resistance between the electrodes becomes sufficiently low. In addition, when the outermost layer is a gold layer, the thinner the gold layer, the lower the cost.

[0103] The thickness of the conductive part can be measured by observing the cross section of the conductive particle using, for example, a transmission electron microscope (TEM). The thickness of the conductive part is preferably calculated as the average value of the thicknesses of five arbitrary conductive parts as the thickness of the conductive part of one conductive particle, and more preferably calculated as the average value of the thickness of the entire conductive part as the thickness of the conductive part of one conductive particle. The thickness of the conductive part is preferably determined by calculating the average thickness of the conductive part of each of 10 arbitrary conductive particles.

[0104] Core material: The conductive particles preferably have protrusions on the outer surface of the conductive part. The conductive particles more preferably have a plurality of protrusions on the outer surface of the conductive part. The conductive particles have a plurality of protrusions on the outer surface of the conductive part, so that the reliability of conduction between the electrodes can be further improved. An oxide film is often formed on the surface of the electrodes connected by the conductive particles. Furthermore, an oxide film is often formed on the surface of the conductive part of the conductive particles. By using the conductive particles having the protrusions, the conductive particles are placed between the electrodes, and then the electrodes are pressed together, so that the oxide film is effectively removed by the protrusions. Therefore, the electrodes and the conductive particles can be more reliably contacted, and the connection resistance between the electrodes can be more effectively reduced. Furthermore, when the conductive particles have an insulating material on the surface, or when the conductive particles are dispersed in a binder resin and used as a conductive material, the insulating material or binder resin between the conductive particles and the electrodes is effectively removed by the protrusions of the conductive particles. Therefore, the reliability of conduction between the electrodes can be more effectively improved.

[0105] By embedding the core material in the conductive portion, a plurality of protrusions can be easily formed on the outer surface of the conductive portion, although it is not necessary to use a core material to form protrusions on the surface of the conductive portion of the conductive particle.

[0106] The method for forming protrusions on the surface of the conductive particles includes a method of adhering a core material to the surface of a resin particle and then forming a conductive part by electroless plating, and a method of forming a conductive part on the surface of a resin particle by electroless plating, adhering a core material, and further forming a conductive part by electroless plating, etc. Also, the core material does not have to be used to form the protrusions.

[0107] Methods for forming the above-mentioned protrusions include the following: A method of adding a core substance at an intermediate stage of forming a conductive part on the surface of a resin particle by electroless plating. A method for forming protrusions by electroless plating without using a core substance includes generating metal nuclei by electroless plating, attaching the metal nuclei to the surface of a resin particle or a conductive part, and further forming a conductive part by electroless plating.

[0108] The material of the core material is not particularly limited. Examples of the material of the core material include conductive materials and non-conductive materials. Examples of the conductive materials include metals, metal oxides, conductive non-metals such as graphite, and conductive polymers. Examples of the conductive polymers include polyacetylene. Examples of the non-conductive materials include silica, alumina, barium titanate, and zirconia. Metals are preferred because they can increase the conductivity and effectively reduce the connection resistance. The core material is preferably a metal particle. As the metal material of the core material, the metals listed as the metals for forming the conductive portion can be appropriately used.

[0109] Insulating material: The conductive particles preferably further comprise an insulating material disposed on the outer surface of the conductive portion. In this case, when the conductive particles are used for connecting the electrodes, short-circuiting between adjacent electrodes can be further prevented. Specifically, when a plurality of conductive particles contact each other, an insulating material exists between the plurality of electrodes, so that short-circuiting between adjacent electrodes in the horizontal direction, rather than between upper and lower electrodes, can be prevented. In addition, when connecting the electrodes, the insulating material between the conductive portion of the conductive particles and the electrodes can be easily removed by pressing the conductive particles with two electrodes. When the conductive particles have a plurality of protrusions on the outer surface of the conductive portion, the insulating material between the conductive portion of the conductive particles and the electrodes can be further easily removed.

[0110] The insulating material is preferably insulating particles, since this allows the insulating material to be removed more easily when the electrodes are pressed together.

[0111] Examples of the insulating material include polyolefin compounds, (meth)acrylate polymers, (meth)acrylate copolymers, block polymers, thermoplastic resins, crosslinked thermoplastic resins, thermosetting resins, water-soluble resins, etc. Only one type of insulating material may be used, or two or more types may be used in combination.

[0112] Examples of the polyolefin compound include polyethylene, ethylene-vinyl acetate copolymer, and ethylene-acrylic acid ester copolymer. Examples of the (meth)acrylate polymer include polymethyl (meth)acrylate, polydodecyl (meth)acrylate, and polystearyl (meth)acrylate. Examples of the block polymer include polystyrene, styrene-acrylic acid ester copolymer, SB type styrene-butadiene block copolymer, SBS type styrene-butadiene block copolymer, and hydrogenated products thereof. Examples of the thermoplastic resin include vinyl polymer and vinyl copolymer. Examples of the thermosetting resin include epoxy resin, phenol resin, and melamine resin. Examples of the crosslinking of the thermoplastic resin include the introduction of polyethylene glycol methacrylate, alkoxylated trimethylolpropane methacrylate, and alkoxylated pentaerythritol methacrylate. Examples of the water-soluble resin include polyvinyl alcohol, polyacrylic acid, polyacrylamide, polyvinylpyrrolidone, polyethylene oxide, and methyl cellulose. In addition, a chain transfer agent may be used to adjust the degree of polymerization. Examples of the chain transfer agent include thiol and carbon tetrachloride.

[0113] The method of disposing the insulating material on the surface of the conductive part includes a chemical method, and a physical or mechanical method. The chemical method includes, for example, an interfacial polymerization method, a suspension polymerization method in the presence of particles, and an emulsion polymerization method. The physical or mechanical method includes a method using spray drying, hybridization, an electrostatic adhesion method, a spraying method, a dipping method, and a vacuum deposition method. Since the insulating material is difficult to be removed, a method of disposing the insulating material on the surface of the conductive part via a chemical bond is preferable.

[0114] The outer surface of the conductive part and the surface of the insulating material may each be coated with a compound having a reactive functional group. The outer surface of the conductive part and the surface of the insulating material may not be directly chemically bonded, and may be indirectly chemically bonded by a compound having a reactive functional group. After a carboxyl group is introduced onto the outer surface of the conductive part, the carboxyl group may be chemically bonded to a functional group on the surface of the insulating material via a polymer electrolyte such as polyethyleneimine.

[0115] (Conductive materials) The conductive material according to the present invention includes the conductive particles and a binder. The conductive particles include the resin particles and a conductive portion disposed on the surface of the resin particles. The conductive particles are preferably dispersed in a binder and used, and are preferably dispersed in a binder and used as a conductive material. The conductive material is preferably an anisotropic conductive material. The conductive material is preferably used for electrical connection between electrodes. The conductive material is preferably a conductive material for circuit connection.

[0116] The binder resin is not particularly limited. As the binder resin, a known insulating resin is used. The binder resin preferably contains a thermoplastic component (thermoplastic compound) or a curable component, and more preferably contains a curable component. The curable component includes a photocurable component and a thermosetting component. The photocurable component preferably contains a photocurable compound and a photopolymerization initiator. The thermosetting component preferably contains a thermosetting compound and a thermosetting agent. Examples of the binder resin include a vinyl resin, a thermoplastic resin, a curable resin, a thermoplastic block copolymer, and an elastomer. Only one type of the binder resin may be used, or two or more types may be used in combination.

[0117] Examples of the vinyl resin include vinyl acetate resin, acrylic resin, and styrene resin. Examples of the thermoplastic resin include polyolefin resin, ethylene-vinyl acetate copolymer, and polyamide resin. Examples of the curable resin include epoxy resin, urethane resin, polyimide resin, and unsaturated polyester resin. The curable resin may be a room temperature curable resin, a thermosetting resin, a photocurable resin, or a moisture curable resin. The curable resin may be used in combination with a curing agent. Examples of the thermoplastic block copolymer include styrene-butadiene-styrene block copolymer, styrene-isoprene-styrene block copolymer, hydrogenated product of styrene-butadiene-styrene block copolymer, and hydrogenated product of styrene-isoprene-styrene block copolymer. Examples of the elastomer include styrene-butadiene copolymer rubber, and acrylonitrile-styrene block copolymer rubber.

[0118] In addition to the conductive particles and the binder resin, the conductive material may contain various additives such as, for example, a filler, an extender, a softener, a plasticizer, a polymerization catalyst, a curing catalyst, a colorant, an antioxidant, a heat stabilizer, a light stabilizer, an ultraviolet absorber, a lubricant, an antistatic agent, and a flame retardant.

[0119] The method for dispersing the conductive particles in the binder resin is not particularly limited and may be a conventionally known dispersion method. Examples of the method for dispersing the conductive particles in the binder resin include the following methods. A method in which the conductive particles are added to the binder resin and then kneaded and dispersed with a planetary mixer or the like. A method in which the conductive particles are uniformly dispersed in water or an organic solvent using a homogenizer or the like, then added to the binder resin, and then kneaded and dispersed with a planetary mixer or the like. A method in which the binder resin is diluted with water or an organic solvent, then the conductive particles are added, and then kneaded and dispersed with a planetary mixer or the like.

[0120] The viscosity (η25) of the conductive material at 25°C is preferably 30 Pa·s or more, more preferably 50 Pa·s or more, and preferably 400 Pa·s or less, more preferably 300 Pa·s or less. When the viscosity of the conductive material at 25°C is equal to or more than the lower limit and equal to or less than the upper limit, the connection reliability between electrodes can be more effectively improved. The viscosity (η25) can be appropriately adjusted by the types and amounts of the blended components.

[0121] The viscosity (η25) can be measured, for example, using an E-type viscometer ("TVE22L" manufactured by Toki Sangyo Co., Ltd.) under conditions of 25° C. and 5 rpm.

[0122] The conductive material can be used as a conductive paste, a conductive film, or the like. When the conductive material according to the present invention is a conductive film, a film not containing conductive particles may be laminated on a conductive film containing conductive particles. The conductive paste is preferably an anisotropic conductive paste. The conductive film is preferably an anisotropic conductive film.

[0123] In 100% by weight of the conductive material, the content of the binder resin is preferably 10% by weight or more, more preferably 30% by weight or more, even more preferably 50% by weight or more, particularly preferably 70% by weight or more, and is preferably 99.99% by weight or less, more preferably 99.9% by weight or less. When the content of the binder resin is equal to or more than the lower limit and equal to or less than the upper limit, the conductive particles are efficiently arranged between the electrodes, and the connection reliability of the connection target members connected by the conductive material is further increased.

[0124] In 100% by weight of the conductive material, the content of the conductive particles is preferably 0.01% by weight or more, more preferably 0.1% by weight or more, and is preferably 80% by weight or less, more preferably 60% by weight or less, even more preferably 40% by weight or less, even more preferably 20% by weight or less, and particularly preferably 10% by weight or less. When the content of the conductive particles is equal to or more than the lower limit and equal to or less than the upper limit, the connection resistance between the electrodes can be more effectively reduced, and the connection reliability between the electrodes can be more effectively increased.

[0125] (Connection structure) A connection structure can be obtained by connecting members to be connected using the above-mentioned conductive particles or a conductive material containing the above-mentioned conductive particles and a binder resin.

[0126] The connection structure includes a first connection target member having a first electrode on its surface, a second connection target member having a second electrode on its surface, and a connection portion connecting the first connection target member and the second connection target member. In the connection structure, the connection portion is formed of conductive particles or is formed of a conductive material containing the conductive particles and a binder resin. The conductive particles include the above-mentioned resin particles and a conductive portion disposed on the surface of the resin particles. In the connection structure, the first electrode and the second electrode are electrically connected by the conductive particles.

[0127] When the conductive particles are used alone, the connection part itself is a conductive particle. That is, the first connection target member and the second connection target member are connected by the conductive particles. The conductive material used to obtain the connection structure is preferably an anisotropic conductive material.

[0128] FIG. 4 is a cross-sectional view showing an example of a connection structure using conductive particles according to the first embodiment of the present invention.

[0129] The connection structure 41 shown in Fig. 4 includes a first connection target member 42, a second connection target member 43, and a connection portion 44 connecting the first connection target member 42 and the second connection target member 43. The connection portion 44 is formed of a conductive material including conductive particles 1 and a binder resin. In Fig. 4, the conductive particles 1 are shown in a schematic manner for convenience of illustration. Instead of the conductive particles 1, conductive particles other than the conductive particles 21 and 31 may be used.

[0130] The first connection target member 42 has a plurality of first electrodes 42a on its surface (upper surface). The second connection target member 43 has a plurality of second electrodes 43a on its surface (lower surface). The first electrodes 42a and the second electrodes 43a are electrically connected by one or more conductive particles 1. Therefore, the first and second connection target members 42 and 43 are electrically connected by the conductive particles 1.

[0131] The manufacturing method of the connection structure is not particularly limited. An example of the manufacturing method of the connection structure includes a method of arranging the conductive material between a first connection target member and a second connection target member, obtaining a laminate, and then heating and pressurizing the laminate. The pressure during the pressurization is preferably 40 MPa or more, more preferably 60 MPa or more, and preferably 90 MPa or less, more preferably 70 MPa or less. The temperature during the heating is preferably 80°C or more, more preferably 100°C or more, and preferably 140°C or less, more preferably 120°C or less.

[0132] The first and second connection target members are not particularly limited. Specific examples of the first and second connection target members include electronic components such as semiconductor chips, semiconductor packages, LED chips, LED packages, capacitors, and diodes, as well as electronic components such as resin films, printed circuit boards, flexible printed circuit boards, flexible flat cables, rigid flexible boards, glass epoxy boards, and glass boards. The first and second connection target members are preferably electronic components.

[0133] The conductive material is preferably a conductive material for connecting electronic components. The conductive paste is preferably a conductive material in a paste form, and is preferably applied in a paste form onto the connection target members.

[0134] The conductive particles, the conductive material and the connection material are also suitable for use in touch panels. Therefore, the connection target member is preferably a flexible substrate or a connection target member having electrodes arranged on the surface of a resin film. The connection target member is preferably a flexible substrate, and is preferably a connection target member having electrodes arranged on the surface of a resin film. When the flexible substrate is a flexible printed circuit board or the like, the flexible substrate generally has electrodes on its surface.

[0135] Examples of the electrodes provided on the connection target members include metal electrodes such as gold electrodes, nickel electrodes, tin electrodes, aluminum electrodes, copper electrodes, molybdenum electrodes, silver electrodes, SUS electrodes, and tungsten electrodes. When the connection target members are flexible printed circuit boards, the electrodes are preferably gold electrodes, nickel electrodes, tin electrodes, silver electrodes, or copper electrodes. When the connection target members are glass substrates, the electrodes are preferably aluminum electrodes, copper electrodes, molybdenum electrodes, or tungsten electrodes. When the electrodes are aluminum electrodes, they may be electrodes made of aluminum only, or may be electrodes in which an aluminum layer is laminated on the surface of a metal oxide layer. Examples of materials for the metal oxide layer include indium oxide doped with a trivalent metal element and zinc oxide doped with a trivalent metal element. Examples of the trivalent metal element include Sn, Al, and Ga.

[0136] The resin particles can be suitably used as a spacer for a liquid crystal display element. The first connection target member may be a first member for a liquid crystal display element. The second connection target member may be a second member for a liquid crystal display element. The connection portion may be a seal portion that seals the outer periphery of the first member for a liquid crystal display element and the second member for a liquid crystal display element in a state in which the first member for a liquid crystal display element and the second member for a liquid crystal display element face each other.

[0137] The resin particles can also be used in a peripheral sealant for liquid crystal display elements. The liquid crystal display element includes a first member for liquid crystal display elements and a second member for liquid crystal display elements. The liquid crystal display element further includes a seal part that seals the outer periphery of the first member for liquid crystal display elements and the second member for liquid crystal display elements in a state in which the first member for liquid crystal display elements and the second member for liquid crystal display elements face each other, and liquid crystal disposed inside the seal part between the first member for liquid crystal display elements and the second member for liquid crystal display elements. In this liquid crystal display element, a liquid crystal dropping method is applied, and the seal part is formed by thermally curing a sealant for the liquid crystal dropping method.

[0138] The above liquid crystal display element is 1 mm 2 The arrangement density of the spacers for the liquid crystal display element per unit area is preferably 10 pieces / mm 2 More preferably, 1000 pieces / mm 2 The above arrangement density is 10 pieces / mm 2 When the arrangement density is 1000 pieces / mm or more, the cell gap becomes more uniform. 2 When the thickness is equal to or less than this, the contrast of the liquid crystal display element becomes even better.

[0139] (Electronic component equipment) The above-mentioned resin particles or conductive particles can be disposed between the first ceramic member and the second ceramic member on the outer periphery of the first ceramic member and the second ceramic member, and can also be used as a gap control material and a conductive connecting material.

[0140] Fig. 5 is a cross-sectional view showing an example of an electronic component device using the resin particles according to the present invention, Fig. 6 is a cross-sectional view showing an enlarged joint portion of the electronic component device shown in Fig. 5.

[0141] An electronic component device 81 shown in FIGS. 5 and 6 includes a first ceramic member 82, a second ceramic member 83, a joint portion 84, an electronic component 85, and a lead frame 86.

[0142] The first and second ceramic members 82 and 83 are each formed of a ceramic material. The first and second ceramic members 82 and 83 are each, for example, a housing. The first ceramic member 82 is, for example, a substrate. The second ceramic member 83 is, for example, a lid. The first ceramic member 82 has a convex portion protruding toward the second ceramic member 83 side (upper side) on the outer periphery. The first ceramic member 82 has a concave portion on the second ceramic member 83 side (upper side) that forms an internal space R for accommodating an electronic component 85. The first ceramic member 82 may not have a convex portion. The second ceramic member 83 has a convex portion protruding toward the first ceramic member 82 side (lower side) on the outer periphery. The second ceramic member 83 has a concave portion on the first ceramic member 82 side (lower side) that forms an internal space R for accommodating an electronic component 85. The second ceramic member 83 may not have a convex portion. The first ceramic member 82 and the second ceramic member 83 form an internal space R.

[0143] The bonding portion 84 bonds an outer periphery of the first ceramic member 82 to an outer periphery of the second ceramic member 83. Specifically, the bonding portion 84 bonds a convex portion of the outer periphery of the first ceramic member 82 to a convex portion of the outer periphery of the second ceramic member 83.

[0144] A package is formed by first and second ceramic members 82, 83 joined by a joint 84. An internal space R is formed by the package. The joint 84 seals the internal space R liquid-tightly and air-tightly. The joint 84 is a sealing portion.

[0145] The electronic component 85 is disposed in the internal space R of the package. Specifically, the electronic component 85 is disposed on the first ceramic member 82. In this embodiment, two electronic components 85 are used.

[0146] The bonding portion 84 includes a plurality of resin particles 11 and glass 84B. The bonding portion 84 is formed using a bonding material including a plurality of resin particles 11 different from glass particles and glass 84B. This bonding material is a bonding material for ceramic packages. The bonding material may include the conductive particles described above instead of the resin particles.

[0147] The bonding material may contain a solvent or may contain a resin. In the bonding portion 84, glass 84B such as glass particles is melted and bonded, and then solidified.

[0148] Examples of the electronic components include sensor elements, MEMS, bare chips, etc. Examples of the sensor elements include pressure sensor elements, acceleration sensor elements, CMOS sensor elements, CCD sensor elements, and housings for the above various sensor elements.

[0149] Lead frame 86 is disposed between the outer periphery of first ceramic member 82 and the outer periphery of second ceramic member 83. Lead frame 86 extends to the internal space R side and the external space side of the package. Terminals of electronic component 85 and lead frame 86 are electrically connected via wires.

[0150] The joint 84 partially directly joins the outer periphery of the first ceramic member 82 to the outer periphery of the second ceramic member 83, and partially indirectly joins them. Specifically, the joint 84 indirectly joins the outer periphery of the first ceramic member 82 to the outer periphery of the second ceramic member 83 via the lead frame 86 in a portion where the lead frame 86 is present between the outer periphery of the first ceramic member 82 and the outer periphery of the second ceramic member 83. In a portion where the lead frame 86 is present between the outer periphery of the first ceramic member 82 and the outer periphery of the second ceramic member 83, the first ceramic member 82 is in contact with the lead frame 86, and the lead frame 86 is in contact with the first ceramic member 82 and the joint 84. Furthermore, the joint 84 is in contact with the lead frame 86 and the second ceramic member 83, and the second ceramic member 83 is in contact with the joint 84. The joint 84 directly joins the outer periphery of the first ceramic member 82 to the outer periphery of the second ceramic member 83 in a portion where there is no lead frame 86 between the outer periphery of the first ceramic member 82 and the outer periphery of the second ceramic member 83. The joint 84 contacts the first ceramic member 82 and the second ceramic member 83 in a portion where there is no lead frame 86 between the outer periphery of the first ceramic member 82 and the outer periphery of the second ceramic member 83.

[0151] In the portion where the lead frame 86 is located between the outer periphery of the first ceramic member 82 and the outer periphery of the second ceramic member 83, the distance of the gap between the outer periphery of the first ceramic member 82 and the outer periphery of the second ceramic member 83 is controlled by a plurality of resin particles 11 contained in the bonding portion 84.

[0152] The bonding portion may be any portion that directly or indirectly bonds the outer periphery of the first ceramic member to the outer periphery of the second ceramic member, and an electrical connection method other than the use of a lead frame may also be used.

[0153] Like the electronic component device 81, the electronic component device may include, for example, a first ceramic member formed of a ceramic material, a second ceramic member formed of a ceramic material, a joint, and an electronic component. In the electronic component device, the joint may directly or indirectly join an outer periphery of the first ceramic member to an outer periphery of the second ceramic member. In the electronic component device, a package may be formed by the first and second ceramic members joined by the joint. In the electronic component device, the electronic component may be disposed in an internal space of the package, and the joint may include a plurality of resin particles and glass.

[0154] Also, like the bonding material used in the electronic component device 81, the ceramic package bonding material is used to form the bonding portion in the electronic component device and contains resin particles and glass. Note that an electrical connection method that contains only resin particles and does not contain glass may be adopted. The bonding portion may contain the conductive particles described above instead of the resin particles.

[0155] The present invention will be specifically described below with reference to examples and comparative examples, but the present invention is not limited to the following examples.

[0156] ( reference Example 1) (1) Preparation of resin particles Polystyrene (PS) particles with an average particle size of 0.80 μm were prepared as seed particles. 3.9 parts by weight of the polystyrene particles, 500 parts by weight of ion-exchanged water, and 120 parts by weight of a 5% by weight aqueous solution of polyvinyl alcohol were mixed to prepare a mixture (seed particle dispersion). The mixture was dispersed by ultrasonic waves, then placed in a separable flask and stirred uniformly.

[0157] In addition, divinylbenzene (NS Styrene Monomer's "DVB960") was prepared as a crosslinking compound. 2 parts by weight of 2,2'-azobis(methyl isobutyrate) (Wako Pure Chemical Industries, Ltd.'s "V-601") and 2 parts by weight of benzoyl peroxide (NOF Corp.'s "Niper BW") were added to 100 parts by weight of divinylbenzene, and 8 parts by weight of triethanolamine lauryl sulfate, 100 parts by weight of ethanol, and 1000 parts by weight of ion-exchanged water were further added to prepare an emulsion.

[0158] The above emulsion was further added to the above mixture in the separable flask, and the mixture was stirred for 4 hours to allow the seed particles to absorb the monomer, thereby obtaining a suspension containing seed particles swollen with the monomer.

[0159] Thereafter, 490 parts by weight of a 5% by weight aqueous solution of polyvinyl alcohol was added, and heating was started to carry out a reaction at 85° C. for 10 hours to obtain resin particles.

[0160] (2) Preparation of conductive particles The obtained resin particles were washed, classified, and then dried. Then, a nickel layer was formed on the surface of the obtained resin particles by electroless plating to prepare conductive particles. The thickness of the nickel layer was 0.1 μm.

[0161] (3) Preparation of conductive material (anisotropic conductive paste) To prepare the conductive material (anisotropic conductive paste), the following materials were prepared.

[0162] (Conductive material (anisotropic conductive paste)) Thermosetting compound A: Epoxy compound ("EP-3300P" manufactured by Nagase ChemteX Corporation) Thermosetting compound B: Epoxy compound (DIC "EPICLON HP-4032D") Thermosetting compound C: Epoxy compound (Yokkaichi Synthetic Co., Ltd. "Epogose PT", polytetramethylene glycol diglycidyl ether) Heat curing agent: Thermal cation generator (Sanshin Chemical Industry Co., Ltd. San-Aid "SI-60") Filler: Silica (average particle size 0.25 μm)

[0163] The conductive material (anisotropic conductive paste) was prepared as follows.

[0164] (Method of producing conductive material (anisotropic conductive paste)) A mixture was obtained by mixing 10 parts by weight of thermosetting compound A, 10 parts by weight of thermosetting compound B, 15 parts by weight of thermosetting compound C, 5 parts by weight of a thermosetting agent, and 20 parts by weight of a filler. The obtained conductive particles were then added so that the content in the mixture (100% by weight) was 10% by weight, and the mixture was stirred at 2000 rpm for 5 minutes using a planetary stirrer to obtain a conductive material (anisotropic conductive paste).

[0165] (4) Fabrication of connection structure A glass substrate having an aluminum electrode pattern with an L / S of 20 μm / 20 μm on its upper surface was prepared as the first connection target member, and a semiconductor chip having a gold electrode pattern with an L / S of 20 μm / 20 μm (gold electrode thickness 20 μm) on its lower surface was prepared as the second connection target member.

[0166] The conductive material (anisotropic conductive paste) immediately after preparation was applied to the upper surface of the glass substrate to a thickness of 30 μm to form a conductive material (anisotropic conductive paste) layer. Next, the semiconductor chip was laminated on the upper surface of the conductive material (anisotropic conductive paste) layer so that the electrodes faced each other. Thereafter, a pressurized heating head was placed on the upper surface of the semiconductor chip while adjusting the temperature of the head so that the temperature of the conductive material (anisotropic conductive paste) layer was 170° C., and the conductive material (anisotropic conductive paste) layer was cured under conditions of 170° C., 1 MPa, and 15 seconds to obtain a connection structure.

[0167] ( reference Example 2) When preparing the resin particles, 100 parts by weight of divinylbenzene (a cross-linking compound) was changed to 50 parts by weight of divinylbenzene ("DVB960" manufactured by NS Styrene Monomer Co., Ltd.) and 50 parts by weight of pentaerythritol triacrylate ("Light Acrylate PE-4A" manufactured by Kyoeisha Chemical Co., Ltd.). In addition to the above changes, reference In the same manner as in Example 1, resin particles, conductive particles, a conductive material, and a connection structure were obtained.

[0168] ( reference Example 3) When preparing the resin particles, 100 parts by weight of divinylbenzene (a cross-linking compound) was changed to 80 parts by weight of polytetramethylene glycol diacrylate ("Light Acrylate PTMGA-250" manufactured by Kyoeisha Chemical Co., Ltd.). When preparing the resin particles, 20 parts by weight of styrene (manufactured by NS Styrene Monomer Co., Ltd.) was further used as a non-cross-linking compound. In addition to the above changes, reference In the same manner as in Example 1, resin particles, conductive particles, a conductive material, and a connection structure were obtained.

[0169] ( reference Example 4) When preparing the resin particles, 100 parts by weight of divinylbenzene (a cross-linking compound) was changed to 60 parts by weight of 1,4-butanediol dimethacrylate ("Light Ester 1.4BG" manufactured by Kyoeisha Chemical Co., Ltd.). When preparing the resin particles, 40 parts by weight of isobornyl acrylate ("Light Acrylate IB-XA" manufactured by Kyoeisha Chemical Co., Ltd.) was further used as a non-cross-linking compound. In addition to the above changes, reference In the same manner as in Example 1, resin particles, conductive particles, a conductive material, and a connection structure were obtained.

[0170] ( reference Example 5) When preparing the resin particles, 100 parts by weight of divinylbenzene (a cross-linking compound) was changed to 30 parts by weight of polytetramethylene glycol diacrylate (Kyoeisha Chemical Co., Ltd.'s "Light Acrylate PTMGA-250"). When preparing the resin particles, 70 parts by weight of isobornyl acrylate (Kyoeisha Chemical Co., Ltd.'s "Light Acrylate IB-XA") was further used as a non-cross-linking compound. Apart from the above changes, reference In the same manner as in Example 1, resin particles, conductive particles, a conductive material, and a connection structure were obtained.

[0171] ( reference Example 6) When preparing the resin particles, 100 parts by weight of divinylbenzene (a cross-linking compound) was changed to 50 parts by weight of glycerin dimethacrylate (Kyoeisha Chemical Co., Ltd.'s "Light Ester G-101P"). When preparing the resin particles, 50 parts by weight of cyclohexyl methacrylate (Kyoeisha Chemical Co., Ltd.'s "Light Ester CH") was further used as a non-cross-linking compound. In addition to the above changes, reference In the same manner as in Example 1, resin particles, conductive particles, a conductive material, and a connection structure were obtained.

[0172] ( implementation Example 7) When preparing the resin particles, 100 parts by weight of divinylbenzene (crosslinkable compound) was changed to 20 parts by weight of divinylbenzene ("DVB960" manufactured by NS Styrene Monomer Co., Ltd.). When preparing the resin particles, 79.5 parts by weight of cyclohexyl methacrylate ("Light Ester CH" manufactured by Kyoeisha Chemical Co., Ltd.) was used as a non-crosslinkable compound, and 0.5 parts by weight of methacrylic acid ("Light Ester A" manufactured by Kyoeisha Chemical Co., Ltd.) was used as a polymerizable compound having a polar functional group. Other than the above changes, resin particles, conductive particles, conductive materials, and connection structures were obtained in the same manner as in Reference Example 1.

[0173] ( reference Example 8) When preparing the resin particles, polystyrene particles (seed particles) with an average particle diameter of 0.80 μm were changed to polystyrene particles with an average particle diameter of 3 μm. When preparing the resin particles, 100 parts by weight of divinylbenzene (crosslinkable compound) was changed to 5 parts by weight of polytetramethylene glycol diacrylate (Kyoeisha Chemical Co., Ltd.'s "Light Acrylate PTMGA-250"). When preparing the resin particles, 65 parts by weight of isobornyl acrylate (Kyoeisha Chemical Co., Ltd.'s "Light Acrylate IB-XA") was used as a non-crosslinkable compound, and 30 parts by weight of 2-methacryloyloxyethyl acid phosphate (Kyoeisha Chemical Co., Ltd.'s "Light Ester P-1M") was used as a polymerizable compound having a polar functional group. Other than the above changes, reference In the same manner as in Example 1, resin particles were obtained.

[0174] When preparing the conductive particles, the thickness of the nickel layer was changed from 0.1 μm to 1 μm.

[0175] Other than the above changes, conductive particles, conductive materials and connection structures were obtained.

[0176] Comparative Example 1 When preparing the resin particles, 100 parts by weight of divinylbenzene (crosslinkable compound) was changed to 20 parts by weight of divinylbenzene ("DVB960" manufactured by NS Styrene Monomer Co., Ltd.). When preparing the resin particles, 80 parts by weight of cyclohexyl methacrylate ("Light Ester CH" manufactured by Kyoeisha Chemical Co., Ltd.) was further used as a non-crosslinkable compound. In addition to the above changes, reference In the same manner as in Example 1, resin particles, conductive particles, a conductive material, and a connection structure were obtained.

[0177] Comparative Example 2 When preparing the resin particles, polystyrene particles (seed particles) with an average particle diameter of 0.80 μm were changed to polystyrene particles with an average particle diameter of 3 μm. When preparing the resin particles, 100 parts by weight of divinylbenzene (crosslinkable compound) was changed to 7.5 parts by weight of polytetramethylene glycol diacrylate (Kyoeisha Chemical Co., Ltd.'s "Light Acrylate PTMGA-250"). When preparing the resin particles, 82.5 parts by weight of isobornyl acrylate (Kyoeisha Chemical Co., Ltd.'s "Light Acrylate IB-XA") was further used as a non-crosslinkable compound. Apart from the above changes, reference In the same manner as in Example 1, resin particles were obtained.

[0178] When preparing the conductive particles, the thickness of the nickel layer was changed from 0.1 μm to 1 μm.

[0179] Other than the above changes, conductive particles, conductive materials and connection structures were obtained.

[0180] (evaluation) (1) Particle size of resin particles and conductive particles The particle sizes of the obtained resin particles and conductive particles were measured using a precision particle size distribution measurement device (Beckman Coulter's "Multisizer3").

[0181] (2) Compressive elastic modulus of resin particles The compressive elastic modulus (10% K value and 30% K value) of the obtained resin particles was measured by the above-mentioned method using a microcompression tester (Fisherscope H-100 manufactured by Fischer).

[0182] (3) Compression recovery rate of resin particles The compression recovery rate of the obtained resin particles was measured by the above-mentioned method using a microcompression tester (Fisherscope H-100, manufactured by Fischer).

[0183] (4) Time-of-Flight Secondary Ion Mass Spectrometry (TOF-SIMS) of Resin Particles The obtained resin particles were subjected to time-of-flight secondary ion mass spectrometry (TOF-SIMS). Specifically, the analysis was performed as follows. For the TOF-SIMS, a "TOF-SIMS 5 model" manufactured by ION TOF was used. The OH groups on the outer surfaces of the resin particles were analyzed using a TOF-SIMS analyzer. - To measure the ionic and total ionic intensities, Bi 3+ An ion gun was used as the primary ion source for measurement, and measurements were performed under conditions of 25 keV. Sputtering was performed by introducing an inert gas such as argon into a vacuum, applying a negative voltage to the target to generate a glow discharge, ionizing the inert gas atoms, and grinding the target surface. By performing sputtering twice, the detection results of each ion intensity in a region about 2 nm thick from the outer surface of the resin particle toward the inside were obtained using TOF-SIMS.

[0184] From the results, when a negative spectrum was obtained by time-of-flight secondary ion mass spectrometry (TOF-SIMS) on the outer surface of the resin particle, the ratio of OH to the total intensity of all negative ions was - Ion intensity ratio (OH - The intensity of the negative ions was calculated as the sum of the intensities of all negative ions.

[0185] (5) Coagulation of resin particles The resin particles were mixed with an organic solvent and the sedimentation rate was measured when the particles were allowed to stand, and the coagulation property of the resin particles was evaluated. 2.5 g of the resin particles were mixed with 25 mL of acetone to prepare a mixed solution, and the mixed solution was dispersed by ultrasonic waves for 1 minute in an ultrasonic cleaner (As One Corporation's "VS-1003"). The mixture was then placed in a 20 mL glass graduated cylinder and allowed to stand. The actual sedimentation rate was calculated by checking the sedimentation of the resin particles every 60 minutes. The ratio of the theoretical sedimentation rate to the actual sedimentation rate ([theoretical sedimentation rate (m / h) / actual sedimentation rate (m / h)]) was calculated and evaluated according to the following criteria.

[0186] The theoretical settling velocity was calculated using Stokes' law, which is used when assuming that spherical particles exist as single particles. However, it does not include terms related to the slurry concentration, so they are not taken into consideration.

[0187] Theoretical settling velocity (m / h) = D p 2 (ρ p -ρ f )g / 18η D p : Resin particle diameter (m) ρ p : Density of resin particles (kg / m 3 ) ρ f : density of acetone (kg / m 3 ):784kg / m 3 g: Gravitational acceleration (m / s) η: Viscosity of acetone (kg / m s): 0.00032 kg / m s

[0188] The density of the resin particles was measured using a dry automatic density meter (Shimadzu Corporation's "AccuPic"). The resin particles were immersed in 100 g of methanol at 25°C for 20 hours and then vacuum-dried at 40°C for 12 hours.

[0189] [Criteria for determining the cohesiveness of resin particles] ○: The above ratio ([theoretical settling velocity (m / h) / measured settling velocity (m / h)]) is less than 0.55 (no agglomerates of resin particles are observed) △: The ratio ([theoretical settling velocity (m / h) / measured settling velocity (m / h)]) is 0.55 or more and less than 0.75 (very few aggregates of resin particles are observed) ×: The ratio ([theoretical settling velocity (m / h) / measured settling velocity (m / h)]) is 0.75 or more (aggregates of resin particles are observed)

[0190] (6) Thickness of conductive part The obtained conductive particles were added to Kulzer's "Technovit 4000" so that the content was 30% by weight, and dispersed to prepare an embedding resin for testing. A cross section of the conductive particles was cut out using an ion milling device (Hitachi High-Technologies Corporation's "IM4000") so as to pass through the center of the conductive particles dispersed in the embedding resin for testing.

[0191] Then, using a field emission transmission electron microscope (FE-TEM) (JEM-ARM200F manufactured by JEOL Ltd.), the image magnification was set to 50,000 times, 10 conductive particles were randomly selected, and the conductive part of each conductive particle was observed. The thickness of the conductive part of each conductive particle was measured, and the arithmetic average was calculated to obtain the thickness of the conductive part.

[0192] (7) Adhesion between resin particles and conductive parts The conductive particles in the connection of the obtained connection structure were observed using a scanning electron microscope (Regulus8220 manufactured by Hitachi High-Technologies Corporation). The conductive parts arranged on the surfaces of the resin particles were checked for cracks or peeling. The number of conductive particles observed was 100. The adhesion between the resin particles and the conductive parts was evaluated according to the following criteria.

[0193] [Criteria for determining adhesion between resin particles and conductive parts] ○○○: 0 conductive particles with cracks or peeling of the conductive part ○○: The number of conductive particles with cracks or peeling in the conductive part is more than 0 and 15 or less ○: More than 15 conductive particles with cracks or peeling of the conductive part and 30 or less △: The number of conductive particles with cracks or peeling in the conductive part is more than 30 and less than 50 ×: More than 50 conductive particles have experienced cracks or peeling of the conductive part.

[0194] (8) Connection reliability (between upper and lower electrodes) The connection resistance between the upper and lower electrodes of the 100 connection structures obtained was measured by the four-terminal method. The average connection resistance was calculated. Note that, based on the relationship of voltage = current x resistance, the connection resistance can be calculated by measuring the voltage when a constant current is passed. The connection reliability was evaluated according to the following criteria.

[0195] [Connection reliability criteria] ○○○: The average connection resistance is 1.5Ω or less ○○: The average connection resistance is over 1.5Ω and 2.0Ω or less ○: The average connection resistance is greater than 2.0Ω and less than 5.0Ω △: The average connection resistance is over 5.0Ω and 10Ω or less ×: The average connection resistance exceeds 10 Ω

[0196] (9) Connection reliability after high temperature and high humidity conditions One hundred connection structures obtained in the above (8) evaluation of connection reliability were left at 85°C and 85% RH for 100 hours. After leaving the connection structures, the 100 connection structures were evaluated for the presence or absence of electrical continuity defects between the upper and lower electrodes. The connection reliability after high temperature and high humidity conditions was evaluated according to the following criteria.

[0197] [Criteria for determining connection reliability after high temperature and high humidity conditions] XX: Out of 100 connection structures, the number of those with poor continuity is 1 or less ○: The number of conductive defects is 2 to 5 out of 100 connection structures. △: Of 100 connection structures, the number of those with poor conduction is 6 to 10. ×: Of 100 connection structures, the number of those with poor conduction was 11 or more.

[0198] Example 7, Reference example 1~ 6, The materials used to prepare the resin particles of Example 8 and Comparative Examples 1 and 2 are shown in Tables 1 and 2. The results are shown in Tables 3 and 4 below.

[0199] [Table 1]

[0200] [Table 2]

[0201] [Table 3]

[0202] [Table 4]

[0203] (10) Example of use as a gap control spacer Preparation of bonding materials for ceramic packages: Example 7, Reference example 1~ 6, In step 8, a bonding material for ceramic packages was obtained containing 30 parts by weight of the obtained resin particles and 70 parts by weight of glass (composition: Ag-V-Te-WPW-Ba-O, melting point 264° C.).

[0204] Fabrication of electronic device: The obtained bonding material was used to fabricate the electronic component device shown in Fig. 5. Specifically, the bonding material was applied to the outer periphery of the first ceramic member by screen printing. Then, the second ceramic member was placed facing the first ceramic member, and the bonding portion was irradiated with a semiconductor laser for firing, thereby bonding the first ceramic member and the second ceramic member.

[0205] In the obtained electronic component device, the distance between the first ceramic member and the second ceramic member was well regulated. The obtained electronic component device also operated well. The airtightness inside the package was also well maintained. The resin particles were well dispersed in the joints. [Explanation of symbols]

[0206] 1...Conductive particles 2...Conductive part 11...Resin particles 21...Conductive particles 22...Conductive part 22A…First conductive part 22B...Second conductive part 31...Conductive particles 31a...protrusion 32...Conductive part 32a...Protrusion 33…core substance 34...Insulating material 41...Connection structure 42...First connection target member 42a...first electrode 43...Second connecting member 43a...second electrode 44…Connection 81...Electronic component device 82...first ceramic member 83...Second ceramic member 84...Joint part 84B…Glass 85...Electronic components 86…Lead frame R…Internal space

Claims

1. A polymer of a polymerizable component containing a plurality of polymerizable compounds, the polymerizable component constituting the polymer contains less than 30% by weight of a crosslinkable compound relative to 100% by weight of the polymerizable component, the polymerizable component constituting the polymer contains a polymerizable compound having a polar functional group in an amount of 0.5% by weight or more and 30% by weight or less based on 100% by weight of the polymerizable component, the crosslinkable compound comprises divinylbenzene, the polymerizable compound having a polar functional group includes a polymerizable compound having a hydroxyl group (excluding a polymerizable compound having a phosphoric acid group) or a polymerizable compound having a carboxyl group; When a negative spectrum is obtained on the outer surface of a resin particle by time-of-flight secondary ion mass spectrometry, the ratio of OH to the total intensity of all negative ions is - The ratio of ion intensities is 2.0 x 10 -2 That's all. Resin particles having a compressive elastic modulus of 1000 N / mm 2 or more when compressed by 10%.

2. The compressive elastic modulus when the resin particles are compressed by 10% is 1000 N / mm 2 More than 4500N / mm 2 The resin particles according to claim 1, wherein:

3. The compressive elastic modulus when the resin particles are compressed by 30% is 300 N / mm 2 More than 4000N / mm 2 The resin particles according to claim 1 or 2, wherein:

4. The resin particle according to any one of claims 1 to 3, which is used as a spacer, or is used to obtain a conductive particle having a conductive portion by forming a conductive portion on the surface of the resin particle.

5. A polymer of a polymerizable component containing a plurality of polymerizable compounds, the polymerizable component constituting the polymer contains less than 30% by weight of a crosslinkable compound relative to 100% by weight of the polymerizable component, the polymerizable component constituting the polymer contains a polymerizable compound having a polar functional group in an amount of 0.5% by weight or more and 30% by weight or less based on 100% by weight of the polymerizable component, the crosslinkable compound comprises divinylbenzene, the polymerizable compound having a polar functional group includes a polymerizable compound having a hydroxyl group (excluding a polymerizable compound having a phosphoric acid group) or a polymerizable compound having a carboxyl group; When a negative spectrum is obtained on the outer surface of the resin particle by time-of-flight secondary ion mass spectrometry, the ratio of the intensity of OH − ions to the sum of the intensities of all negative ions is 2.0×10 −2 or more; Resin particles having a compressive elastic modulus of 1000 N / mm 2 or more when compressed by 10% (excluding resin particles used to obtain conductive particles having a conductive portion by forming the conductive portion on the surface).

6. The resin particles according to claim 5, wherein the compressive modulus of elasticity when the resin particles are compressed by 10% is 1000 N / mm 2 or more and 4500 N / mm 2 or less.

7. The resin particles according to claim 5 or 6, wherein the compressive modulus of elasticity when the resin particles are compressed by 30% is 300 N / mm 2 or more and 4000 N / mm 2 or less.

8. A resin particle described in any one of claims 5 to 7, used as a spacer.

9. The resin particles according to any one of claims 1 to 4, and a conductive portion disposed on a surface of the resin particle.

10. The conductive particle of claim 9 , further comprising an insulating material disposed on an outer surface of the conductive portion.

11. The conductive particle according to claim 9 or 10, having protrusions on an outer surface of the conductive portion.

12. The conductive particles and the binder resin are included. A conductive material, comprising the resin particle according to any one of claims 1 to 4 and a conductive portion disposed on a surface of the resin particle.

13. a first connection target member having a first electrode on a surface thereof; a second connection target member having a second electrode on a surface thereof; a connection portion connecting the first connection target member and the second connection target member, the connection portion is formed of conductive particles or a conductive material containing the conductive particles and a binder resin, The conductive particle comprises the resin particle according to any one of claims 1 to 4 and a conductive portion disposed on a surface of the resin particle, A connection structure, wherein the first electrode and the second electrode are electrically connected by the conductive particles.

Citation Information

Patent Citations

  • Metal-coated particle and conductive material

    JP1998259253A

  • Anisotropic conductive bonding ink, liquid crystal display device and method of producing liquid crystal display device

    JP2001135141A

  • Polymer resin fine particles, conductive fine particles, and anisotropically conductive connecting materials containing them

    JP2008521963A

  • Conductive particle, conductive material, and connection structure

    JP2013214509A

  • Conductive particle for touch panel, conductive material for touch panel, and connection structure for touch panel

    JP2014081928A